Digitisation, AI and algorithms in African journalism and media contexts : practice, policy and critical literacies - Dralega, Carol Azungi (Emerald Publishing Limited, 2023)
AI, robots, algorithms, and data/metrics are pervasive throughout the media industry, increasingly dictating and rapidly changing journalistic and newsroom practices, cultures, and norms - from editorial agenda setting to news production processes, to audience and advertiser targeting. Social media platforms in particular have been at the core of the AI and algorithmic turn, offering real-time consumer analytics and newsfeeds for insatiable and borderless digital citizens. The algorithms within these platforms make them powerful news aggregators, redirecting consumer habits and advertisers, making them vital in the journalism practice and media viability across the globe. Despite this, there is a shortage of scholarship on AI, algorithms and data-driven journalism from the global South, and especially in Sub-Saharan African contexts. Digitisation, AI and Algorithms in African Journalism and Media Contexts moves the focus from the West, addressing the significant knowledge gaps relating to the current state of AI, algorithms and data-driven journalism, as well as the implications for political, social, cultural, markets, media viability and journalism education. This timely collection offers new knowledge on key issues surrounding automation and data-driven media and journalism practice in post-truth, post-human and post-Covid African contexts. It is a vital resource for researchers, educators, media students, academics, advocacy groups, media practitioners, developers and policy makers, both in African countries and internationally.